Interdental Consonant Sound Errors Made by First Semester Students of English Education of Sanata Dharma University - Albertus Yordhana Arsanto; Adityo Prawinanto; Barli Bram (Vision: Journal for Language and Foreign Language Learning, 2019)
This paper investigated factors influencing students’ pronunciation. Pronunciation is one of the important aspects of the learning of English. When mastering English pronunciation, many non-native English speakers have difficulty pronouncing certain words that contain the phonemes not used in their native languages. This paper also reported several aspects that might influence pronunciation. The pronunciation aspect investigated in this research paper was the English interdental consonants [θ] and [ð], which are not available in the Indonesian language sound system. This qualitative research used interviews as a method for collecting primary data. The researchers interviewed twenty participants from the English Language Education Study Program (ELESP) of Sanata Dharma University, Yogyakarta, Indonesia, related to the pronunciation of the two interdental consonant sounds. The findings showed that the mother tongue, age, and teacher instruction on target language exposures affected the ELESP students’ (mis)pronunciation. Pedagogical implications of the findings are English teachers can assist their students in overcoming pronunciation challenges involving the two interdental consonants and pronunciation textbook writers should  provide more  pronunciation practices focusing on [θ] and [ð] sounds.